Correlation of severity of tinnitus with severity of anxiety and depression in adults in a tertiary care hospital at Bhuj, Gujarat, India - Khilnani, Ajeet Kumar; Thaddanee, Rekha; Chodvadiya, Manali; Khilnani, Gurudas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Tinnitus may be objective or subjective. Subjective tinnitus is the type most commonly associated with psychosocial co-morbidities. This study was conducted with an aim to assess the severity of tinnitus and to know its correlation with anxiety and depression in adult population of Western Gujarat region. Methods: This prospective observational study was conducted in a tertiary care teaching hospital of Western Gujarat from December 2016 to July 2017. Patients with tinnitus were screened for anxiety and depression using tinnitus handicap inventory (THI, validated in Gujarati language), generalized anxiety disorder (GAD-7) and patient health questionnaire (PHQ-9). Severity of anxiety and depression was further evaluated using The Hamilton anxiety rating scale (HAM-A) and the Hamilton rating scale for depression (HRSD, also called HAM-D) respectively. Results: 68 patients fulfilled the inclusion criterion. Maximum patients (30.9 %) had moderate tinnitus, followed by severe (26.4 %), catastrophic (19.1 %), mild (16.2 %) and slight (7.4 %). There was a strong and significant correlation between the average THI scores and average GAD-7 scores (r=0.9708, p<0.00001) and average THI scores and average PHQ-9 scores (r=0.9906, p<0.0001) suggesting that patients with tinnitus were very likely to have anxiety as well as depression. However, irrespective of the severity of tinnitus, most patients had only mild anxiety (r=0.9403, p<0.00001) and mild depression (r=0.6758, p=0.001). Conclusions: The patients with tinnitus are very likely to suffer from mild anxiety as well as mild depression.